2016
DOI: 10.1111/jgh.13314
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 4‐Fr with 5‐Fr endoscopic nasopancreatic drainage catheters: A randomized, controlled trial

Abstract: Background and Aim: Although endoscopic nasopancreatic drainage (ENPD) is useful for collecting samples for pancreatic juice cytology and for treating leakage of pancreatic juice and occlusive pancreatitis, placement of the ENPD catheter is associated with complications such as post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP). We investigated whether an ENPD catheter with a smaller diameter could reduce the incidence of complications. Methods: Patients requiring placement of an ENPD cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
10
1
Order By: Relevance
“…Regarding complications, PEP occurred in 7% patients, which is similar to the incidence reported previously (3.8-15.1%) [28][29][30]. We have already reported that a 4-Fr ENPD catheter can be used to reduce the risk of PEP [31]. Collection of PJC can be performed in various ways, and we consider that it is a need for complementary use of these methods, depending on the circumstances of pancreatography and abnormal MPD findings.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding complications, PEP occurred in 7% patients, which is similar to the incidence reported previously (3.8-15.1%) [28][29][30]. We have already reported that a 4-Fr ENPD catheter can be used to reduce the risk of PEP [31]. Collection of PJC can be performed in various ways, and we consider that it is a need for complementary use of these methods, depending on the circumstances of pancreatography and abnormal MPD findings.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, 4 patients (11.8%) developed PEP, and no procedure-related deaths were observed. The incidence rate of PEP has been reported to be 4.2% to 12.4% 17,20,22 . Mouri et al 22 reported that 4F ENPD tube was associated with less PEP than 5F ENPD tubes.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,18,20,31 A randomized controlled study comparing 4-Fr with 5-Fr ENPD catheters to reduce the incidence of PEP suggested that an ENPD catheter with a smaller diameter may reduce the incidence of PEP. 42 When EUS demonstrates a hypoechoic lesion around the MPD stenosis, usually the possibility of small invasive PDAC is considered, and the tendency is to perform EUSfine needle aspiration (FNA), initially. However, even if pathologic findings of EUS-FNA are negative, it does not rule out HG-PanIN completely.…”
Section: Preoperative Pathological Diagnosis Of Stage 0 Pdacmentioning
confidence: 99%
“…However, SPACE may be associated with a serious complication, such as post‐ERCP pancreatitis (PEP), with an incidence rate of 0–16% 11,13,18,20,31 . A randomized controlled study comparing 4‐Fr with 5‐Fr ENPD catheters to reduce the incidence of PEP suggested that an ENPD catheter with a smaller diameter may reduce the incidence of PEP 42 …”
Section: Preoperative Pathological Diagnosis Of Stage 0 Pdacmentioning
confidence: 99%